2018
DOI: 10.1007/s00425-018-2968-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of cell-wall composition and RNA-seq transcriptome to methyl-jasmonate in Brachypodium distachyon callus

Abstract: Main conclusionMethyl-jasmonate induces large increases in p-coumarate linked to arabinoxylan in Brachypodium and in abundance of GT61 and BAHD family transcripts consistent with a role in synthesis of this linkage.Jasmonic acid (JA) signalling is required for many stress responses in plants, inducing large changes in the transcriptome, including up-regulation of transcripts associated with lignification. However, less is known about the response to JA of grass cell walls and the monocot-specific features of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…One possibility is that, analogous to the putative role of pCA on lignin discussed below, pCA-GAX may participate in radical transfer, thus catalyzing the oxidative coupling of neighboring FA on GAX. This is compatible with the observation that pCA on GAX rapidly increases in response to jasmonic acid application to Brachypodium callus (Hyde et al, 2018) which could be part of a priming of defense, allowing rapid cross-linking to occur in response to additional signals.…”
Section: Hydroxycinnamate Modification Of Xylansupporting
confidence: 90%
“…One possibility is that, analogous to the putative role of pCA on lignin discussed below, pCA-GAX may participate in radical transfer, thus catalyzing the oxidative coupling of neighboring FA on GAX. This is compatible with the observation that pCA on GAX rapidly increases in response to jasmonic acid application to Brachypodium callus (Hyde et al, 2018) which could be part of a priming of defense, allowing rapid cross-linking to occur in response to additional signals.…”
Section: Hydroxycinnamate Modification Of Xylansupporting
confidence: 90%
“…Since we had previously observed that diferulate (diFA) levels were maintained despite loss of AX in endosperm of RNAi lines (Freeman et al , 2017), we were interested to find a BAHD gene (TaBAHD2A) and a peroxidase gene (TaPRX19D) among the most up‐regulated within endosperm DEGs. BAHD genes in this clade are putatively involved in addition of FA (de Souza et al , 2018) or p ‐coumarate (pCA) to AX (Bartley et al , 2013); we have recently demonstrated that the orthologs of these TaBAHD02 genes are dramatically up‐regulated by methyl‐jasmonate in Brachypodium accompanied by a rise in both FA and pCA linked to AX (Hyde et al , 2018). Tandemly arranged TaBAHD02 paralogues are present on all subgenomes in wheat and were significantly up‐regulated in the endosperm of triple mutants (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the up‐regulation of BAHD02 and peroxidase genes may be responsible for the increased FA per unit AX and FA dimerization that we observed here (Tables 1 and 3) and previously (Freeman et al , 2017) in response to TaIRX9b repression. Brachypodium orthologues of TaBAHD02 and multiple peroxidases were also substantially up‐regulated following methyl‐jasmonate treatment which also induced increases in cell wall pCA, FA and FA dimerization (Hyde et al , 2018). Here, we obtained evidence that the increased amount of diFA per unit AX resulted in greater cross‐linking between WE‐AX molecules from triples, shown by the much greater decrease in molecular weight induced by saponification (Figure 6c).…”
Section: Discussionmentioning
confidence: 99%
“…As imilar stress response was observed in Brachypodium distachyon callus grown hydroponically and stimulated with methyl jasmonate, ap lant stress-response hormone. [62] Biomassand APL compositional analysis To determinet he change in lignin-bound pCA,w ea ssayed isolated lignin from the "best" lines by using 2D HSQC NMR spectroscopy (Table S4). The assays showedas trong correlation between the level of PMT expression and the amounto fl igninbound pCA.…”
Section: Geneticengineering Of Zea Maysmentioning
confidence: 99%